Analisis Kehadiran Generasi Y dan Z dalam Ibadah Sabat di GMAHK Northern Sabah Mission Berdasarkan Mazmur 84 - Zahari, Dj Herjai; Hendriks, Alvyn C. (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This research aims to explore the theological meaning of Psalm 84:2, 3, and 5 and how it relates to understanding the presence of Generations Y and Z in Sabbath worship, especially within the Northern Sabah Mission. By using an exegetical approach to the Hebrew and Greek texts, along with expert interpretations and the historical background of Psalm 84. In today’s context, the study highlights several reasons why younger generations are less involved in Sabbath worship. These include personal and spiritual struggles, worship formats that feel outdated or irrelevant, digital distractions, and church leadership styles that don’t adapt well to modern changes. This research recommends a more holistic and contextual pastoral approach, including: deeper and more personal spiritual mentoring; worship services that are inclusive and meaningful without losing theological depth; building communities that are relational and allow participation, and using digital media as a new space for faith-building and sharing the gospel. Furthermore, actively involving young people in church ministry is seen as key to shaping their spiritual identity.